Importance of intercultural education and competence in learning small languages - Novak Milić, Jasna (Array, 2008)
Based on the results of a specially designed questionnaire and previous research, the authors propose cultural content for the Croatian curriculum that fulfi lls learners’ needs depending on the status of the Croatian language (majority language, official language, neighboring language, heritage language etc.) and their native culture. Conclusions are applicable to other “ small” languages, i.e. cultures, like Croatian.